(untitled) (Alternautas, 2022)
Peruvian Andes, meanings of resistance, reproduction of the racial social order This article explores the controversial aspect of resistance in the Peruvian Andes. Resistance does not necessarily mean subversion of a dominant unjust social order. On the contrary, it can paradoxically endorse it. The case of the Peruvian Andes provides an illustrative example of how resistance in a post-colonial society can play this role. The purpose of this paper is to reflect on the meaning of resistance in contexts imbued with racial prejudice towards the indigenous Other. By illustrating how resistance has implied the reinstatement of an unjust and fundamentally racist social order, it induces researchers to review the understanding of indigenous bottom-up forms of opposition. Not all forms of indigenous resistance unanimously mean that subversion of an unjust and oppressive domination is taking place. Case in point the example of indigenous mobilising in the Peruvian Andes will illustrate this oxymoron. In order to exemplify my argument I take into account various forms of indigenous resistance enacted throughout history. This includes opposition that indigenous peoples have practiced against the consolidation of an intercultural education.